EKSPLOITASI SEKSUAL DALAM PERSPEKTIF ALQURAN (ANALISIS TEOLOGI PEMBEBASAN PEREMPUAN ASGHAR ALI ENGINEER) - Bannan Naelin Najihah; Muhamad Fajar; Abd. Muid Nawawi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2024)
This research examines sexual exploitation in the perspective of the Qur'an which is explored through the analysis of Ashghar Ali Engineer's theology of women's liberation. The research method used in this study uses a descriptive qualitative method with a library research approach and content analysis techniques. QS. An-Nur/24: 33 contains principles that protect individual rights, justice, human equality, privacy rights, social welfare and respect for the dignity of women. This verse emphasizes that every human being is only a slave to Allah and not a slave to other humans and humans will be held accountable for the crimes they commit sexually to others. From the aspect of rejection of the status quo, this verse encourages Muslim communities to oppose the normalization of the weakening of women in a society or system that perpetuates cases of sexual exploitation in various lines such as political, legal, social, economic, or cultural. The value of QS. An-Nur/24: 33 regarding the release of the Prophet Muhammad PBUH against Musaikah and Umaimah and the fight against sexual exploitation can be an inspiration for the revitalization of the process of liberating sexual exploitation cases based on Islamic history.